Antiglycation, antioxidant, antiacne, and photoprotective activities of crude extracts and triterpene saponin fraction of Sapindus saponaria L. fruits: An in vitro study - Silva, Regildo M. G. [UNESP]; Martins, Gustavo R. [UNESP]; Nucci, Laura M.B. [UNESP]; Granero, Filipe O. [UNESP]; Figueiredo, Célia C.M. [UNESP]; Santiago, Patrícia S. [UNESP]; Silva, Luciana P. (Wolters Kluwer, 2022)
Objective: To evaluate the photoprotective, antioxidant, antiglycation, and antiacne activities of crude extract (CESs) and triterpene saponin fraction (TSSs) of Sapindus saponaria. Methods: HPLC-MS purification was performed on a Symmetry TM C18 column. The saponins were identified by a UV detector. Antioxidant activity was evaluated by DPPH and O 2 - radicals scavenging, and FRAP and TBARS assays. Glycation activity was assessed by relative electrophoretic mobility and inhibition of advanced glycation end products (AGEs) formation. Additionally, antiacne activity was determined by inhibition of Cutibacterium acnes, and photoprotective effect was evaluated by Mansur's method. Results: Most of the triterpene saponins detected in the fraction by HPLC-MS analysis were hederagenin as the aglycon. CESs and TSSs presented varying antioxidant activity in DPPH (CESs: 75.69% and TSSs: 83.65%), FRAP (CESs: 425.39 μM TE/g DW and TSSs: 649.36 μM TE/g DW), TBARS (CESs: 42.96% and TSSs: 52.16%) and O 2 - radicals scavenging (CESs: 61.33% and TSSs: 86.69%) tests. CESs and TSSs also exhibited antiglycation activity comparable to bovine serum albumin treated with aminoguanidine. In addition, CESs and TSSs showed inhibition of AGE formation (34.48% and 61.85%, respectively). Antiacne activity against Cutibacterium acnes was observed with a minimum inhibitory concentration equal to minimum bactericidal concentration (CESs: 36.11 μg/mL and TSSs: 18.34 μg/mL). In photoprotective assays, CESs and TSSs showed maximum absorbance of 1.42 to 0.20 and 2.80 to 1.30, respectively, in the wavelength range of 260 to 400 nm. Furthermore, CESs and TSSs showed sun protection factors of 8.89 and 14.89, respectively. Conclusions: Sapindus saponaria fruit extracts show strong antioxidant potential and antiglycation activity against bovine serum albumin glycation and AGE formation. Besides, they presented antibacterial activity against Cutibacterium acnes and photoprotective effect against UV-A and UV-B.
Keywords: AGE formation; Antioxidant; Free radical; Photoprotective; Sapindus saponaria; Triterpene saponin